BPA‐toxicity via superoxide anion overload and a deficit in β‐catenin signaling in human bone mesenchymal stem cells. Issue 1 (29th January 2016) - Leem, Yea‐Hyun; Oh, Seikwan; Kang, Hong‐Je; Kim, Jung‐Hwa; Yoon, Juno; Chang, Jae‐Suk
ABSTRACT: Bisphenol A (BPA), used in the manufacture of products based on polycarbonate plastics and epoxy resins, is well known as an endocrine‐disrupting monomer. In the current study, BPA increased cytotoxicity in hBMSCs in a dose‐ and time‐dependent manner, concomitantly with increased lipid peroxidation. Increased cell death in BPA‐treated cells was markedly blocked by pretreatment with the superoxide dismutase mimetic MnTBAP and MnTMPyP, but not by catalase, glutathione, the glutathione peroxidase mimetic ebselen, the NOS inhibitor NAME, or the xanthine oxidase inhibitor allopurinol. Furthermore, the decline in nuclear β‐catenin and cyclin D1 levels in hBMSCs exposed to BPA was reversed by MnTBAP treatment. Finally, treatment of hBMSCs with the GSK3β inhibitor LiCl2 increased nuclear β‐catenin levels and significantly attenuated cytotoxicity compared with BPA treatment. Our current results in hBMSCs exposed to BPA suggest that BPA causes a disturbance in β‐catenin signaling via a superoxide anion overload. © 2016 The Authors Environmental Toxicology Published by Wiley Periodicals, Inc. Environ Toxicol 32: 344–352, 2017.